Nitrate and Ammonium Leaching in Cool‐Season Turfgrass as Affected by Temperature and Potential Evapotranspiration. (16th August 2017) - Soldat, Douglas J.; Petrovic, A. Martin; Rossi, Frank S.; Barlow, Jeffrey
Abstract : Nitrogen (N) fertilizer is often added to turfgrass during times of low temperature when soil N mineralization cannot meet plant needs. However, the spring and fall in humid temperate regions often receive more precipitation than evapotranspiration (ET). Excess soluble N in the soil has the potential to be leached into groundwater, especially when groundwater is being recharged. Temperature and ET are hypothesized to influence N uptake independently; however, their individual contributions have not been characterized in turfgrass systems. Therefore, the objective of this study was to evaluate ammonium (NH4 –N) and nitrate (NO3 –N) leaching of applied fertilizer from different cool‐season grasses under a wide range of temperature and potential ET conditions observed in the cooler periods of the year in temperate climates. Kentucky bluegrass ( Poa pratensis L.) and a mixture of tall fescue [ Schedonorus arundinaceus (Schreb.) Dumort.] and fine fescue ( Festuca longifolia Tracey) were established in 36‐cm‐deep containers on a sandy loam soil. The treatments were combinations of six temperatures (0, 2, 4, 6, 8, and 10°C) and three potential ET rates (1.0, 2.5, and 5.1 mm d −1 ). Approximately 10 d after a 49‐kg ha −1 application of soluble N, leaching was induced. As temperature and ET decreased (independently), more NO3 –N was recovered in leachate. Ammonium leaching was low and not affected by any factor. ET had a larger influence on NO3 –N leaching at higher temperatures than at lower temperatures. These results suggest that both forecasted temperature and ET could be useful for developing NO3 –N leaching risk assessment models.